Improved methods for assessing the system of weapons and military equipment recovery of a separate mechanized brigade - Sampir , Oleksandr (Social Development and Security, 2021)
The main sources of providing troops with weapons and military equipment (weapons) in the course of hostilities are: production (purchase) of weapons; restoration of damaged weapons; use of pre-established reserve (inviolable stocks) of weapons. Additional sources of armaments in a special period may be: equipment supplied from the national economy; receipt of weapons in the framework of assistance from partner countries; trophy weapons. But, as the experience of fighting during the anti-terrorist operation in the Donetsk and Luhansk regions, directly during the operations (combat operations) supply of armaments is carried out mainly through the restoration of weapons that have failed due to combat or operational reasons. This is due to the financial and economic capabilities of the state, exceeding the service life of weapons, the need for rapid supply of serviceable weapons to maintain the required level of combat readiness of units to perform tasks and a number of other factors affecting the availability and condition of weapons in units and military units. Execution of the task of timely restoration of damaged weapons during combat is entrusted to the system of restoration of weapons and military equipment, which is a complex (large) system containing a control subsystem and executive subsystem, based on forces and means of weapons recovery. In the general case, the forces and means of the weapons recovery system should be understood as the personnel of the repair and restoration bodies and means of technical intelligence, evacuation, repair of weapons used for their timely detection, loading and unloading and transportation works, repair and preparation for combat use, etc. The effective operation of all components of this complex system requires advance planning and preliminary forecasting of the production capacity of these units. Therefore, the article proposes ways to improve the scientific and methodological apparatus for assessing the recovery system and military equipment.